THE POLICY OF USING ENGLISH FOR TEACHING IN INDONESIAN ISLAMIC SCHOOLS: OPPORTUNITIES AND CHALLENGES - Widayani, Gwi; Budianto, Lestari; Damayanti, Elis (Universitas Islam Sumatera Utara (UISU), 2024)
Implementing English as a mandatory language for teaching remains a contentious policy, especially among educators who are not English subject teachers or do not come from the English department. This research investigates the policies, opportunities, and challenges associated with enforcing English language policies in Islamic schools in Indonesia. Using a mixed-method design, the study surveyed 77 participants from various Islamic schools across Indonesia, employing questionnaires, observations, and interviews for data collection. The findings reveal that specific policies in Indonesian Islamic schools can address three key aspects: justification (addressing particular needs and challenges while maximizing benefits and minimizing drawbacks), logic (strategic implementation to optimize outcomes), and feasibility (practicality and achievability of implementing English language policies). Furthermore, English language policies present significant opportunities, such as enhanced global competence, economic empowerment, educational advancement, cultural exchange and understanding, technological integration, and international collaboration and partnerships. However, several challenges hinder the implementation of these policies, including the preservation of cultural identity and values, resource constraints, language proficiency, resistance to change, and assessment and evaluation. Future research is expected to explore new strategies to overcome these challenges and maximize the opportunities of using English in Indonesian Islamic schools, thereby ensuring the success of English language policies.